LITERASI PEMERIKSAAN KEUANGAN PADA UMKM DI KELURAHAN SIDOMULYO KECAMATAN STABAT - Fachruddin, Wan; Aliah, Nur; Rizkina, Miftha; Sitorus, Atika Zuhra (LPPM Institut Teknologi dan Bisnis Kristen Bukit Pengarapan, 2025)
This Community Service Program aims to enhance financial examination literacy among Micro, Small, and Medium Enterprises (MSMEs) in Sidomulyo Village, Stabat District. The main problems faced by MSMEs in this area include limited understanding of basic financial examination, as indicated by inadequate transaction records, poorly organized supporting documents, the mixing of personal and business finances, and the inability to evaluate business financial conditions in a simple and systematic manner. The program was implemented using a participatory approach through socialization activities, interactive training, and direct assistance to MSME owners. The training materials focused on basic concepts of financial examination, identification and verification of transaction evidence, separation of personal and business finances, and the introduction of financial statements based on the MSME Financial Accounting Standards (SAK EMKM) as a foundation for financial evaluation. The evaluation results indicate a significant improvement in participants’ understanding of the importance of financial examination as a tool for financial control and business performance evaluation. Most participants reported increased confidence in managing their business finances in a more orderly and transparent manner. This program represents an initial step in building MSMEs’ awareness of financial examination practices to support more professional and sustainable business management.